Racial Differentials in Male Unemployment Rates: Evidence from Low-Income Urban Areas - Leigh, Duane E.; Rawlins, V. Lane (The Review of Economics and Statistics, 1974)
EXTRAORDINARILY high unemployment among nonwhite teenagers is often explained in terms of the disadvantaged environment from which this group comes. As noted in a recent Manpower Report of the President (1972, p. 80), however, there is a large gap between whites and blacks in the extent of unemployment within urban poverty areas. This suggests that even among males living in the inner-city, racial discrimination in employment may be important in explaining observed racial differentials in unemployment rates. Isolation of the direct impact of race on unemployment is difficult because variations in many factors related to unemployment for both whites and nonwhites are also associated with race as a consequence of generations of discrimination in housing, education, employment, and participation in social and political processes. This study attempts to measure the direct impacts of race and age in determining racial differentials in unemployment rates among males aged 16-21 and 22-34 years residing in urban low-income areas. The older group of males is examined because while the unemployment rates of both whites and blacks drop sharply as teenagers become young adults, the unemployment rate of blacks in recent years has fallen further than that of whites resulting in a lower black-white ratio 'of unemployment rates for the older age category (see Leigh and Rawlins, 1973). Two specific issues are addressed in the paper. (1) How much of racial unemployment rate differentials can be explained by race after standardization by employment-related personal characteristics, and how does the magnitude of the differentials explained by race differ across age groups? (2) How much of the lower unemployment rates observed for the older age group can be attributed to age after standardization, and does the effect of aging differ by race? In approaching these questions we utilize a new source of data, the Census Employment Survey (CES) (United States Bureau of the Census, 1972), recently made available as a part of the 1970 Census. The survey provides data from persons living in 60 selected lowincome areas in 51 large cities and 7 rural areas.1 Approximately half the respondents are black and nearly 12 % are Spanish-speaking (largely Puerto Ricans, Chicanos, and Cubans). For the purposes of this study, CES data offer the advantage, relative to Census data, of providing more information on job training, job-seeking methods, job tenure, and other cognitive skills usually thought to be associated with success in the labor market.